Purification and characterization of α‐acetolactate decarboxylase (ALDC) from newly isolated Lactococcus lactis DX. (2nd September 2014) - Guo, Yuxing; Pan, Daodong; Ding, Haibing; Wu, Zhen; Sun, Yangying; Zeng, Xiaoqun
Abstract BACKGROUND Diacetyl (2, 3‐butanedione) is a common flavor aroma from fermented dairy products. There is a need to screen new microorganisms that can efficiently produce large amounts of diacetyl. RESULTS A new lactic acid bacterium that produced high concentrations of diacetyl was identified based on Gram staining, microscopic examination and 16S rDNA sequence analysis as Lactococcus lactis DX. Its α‐acetolactate decarboxylase (ALDC) was purified using 0.45 g mL−1 ammonium sulfate precipitation, Sephacryl S‐300 and S‐200 HR and native‐PAGE. The purified ALDC displayed a monomer structure and had a molecular mass of about 73.1 kDa, which was estimated using SDS‐PAGE. IR analysis showed that the ALDC had a typical protein structure. The optimal temperature and pH for ALDC activity were 40 °C and 6.5 respectively. The ALDC of L. lactis DX was activated by Fe2+, Zn2+, Mg2+, Ba2+ and Ca2+, while Cu2+ significantly inhibited ALDC activity. Leucine, valine and isoleucine activated the ALDC. CONCLUSION A strain that had high ability to produce diacetyl was identified as L. lactis DX. The difference in diacetyl production may be due to the ALDC, which is different from other ALDCs. © 2014 Society of Chemical Industry